Desenvolvimento, validação e confiabilidade de uma escala de dor aguda pós-operatória em bovinos - Oliveira, Flávia Augusta de [UNESP] (2014)
Pain has been historically neglected in animals and its recognition and quantification remains a challenge to be overcome, especially in large animals. This study aimed to record behaviors and define the validity and reliability of an acute postoperative pain scale in cattle. Forty cattle underwent orchiectomy with sedation and local anesthesia. Animals were evaluated and filmed before and after the surgical procedure. The videos were viewed and behaviors were recorded. Additionally, a pedometer was adapted on the limb of each animal to record the number of steps, time of lying down and number of times to get decubitus. These data were used to correlate or not with the experience of pain in the postoperative period. The scale was based on previous studies, pilot study and video records analysis. Animals were evaluated by movies in preoperative (M1) and postoperatively period, before (M2) and after rescue analgesia (M3) and 24 hours after surgery (M4). Three blinded and one gold standard observers evaluated the movies, which were revalued one month after the first analysis. Difference in the number of times to get decubitus between 24 hours before and after the surgical procedure was detected. The refinement of the scale was determined by criterion validity. This was attested by agreement between each blinded observers and the gold standard, so the items standing posture and head position were excluded for not having satisfactory agreement. Factor analysis determined the dimensionality of the scale, resulting in a unidimensional scale. Item-total correlation by Spearman rank correlation coefficient determined the exclusion of the item attention to surgical wound. After refinement, internal consistency was assessed by calculating the Cronbach α coefficient (α = 0.866) and was considered excellent. UNESP-Botucatu unidimensional pain scale was correlated with visual analogic, descriptive and numerical ...